Penerapan Decision Making NPC dengan Metode Hierarchical Finite State Machine Pada 2D Endless Runner Game - Mayovio Ahmad Mahendrata; Eriq Muh. Adams Jonemaro; Muhammad Aminul Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Video game with 2D endless runner genre is one of the genre that is still popular today. In this 2D endless runner game, players are required to walk forward without stopping by passing platforms and obstacles in the form of traps and Non-Player Character (NPC) that act as player enemies. The NPC in this game will have an artificial intelligence that is applied to the decision making of the NPC. The method used in this NPC decision making is the Hierarchical Finite State Machine (HFSM). Decision making from NPC will be implemented by creating states and sub-states. This state will move to another state based on triggers received by the NPC, while the sub-state moves not only with triggers, but also based on the current state. This movement from one state to another uses a transition. The state and sub-state of the NPC will affect the behavior of the NPC, which can affect the playability and provide an increase in the performance of the game itself. The result is that the most optimum frame rate produced is 68.3 fps with an NPC of 25. This is in accordance with the average minimum frame rate that is standardized in the game, which is 30 fps.